Cell cycle defects in polyhomeotic mutants are caused by abrogation of the DNA damage checkpoint. - Beck, S.A.; Falconer, E.; Catching, A.; Hodgson, J.W.; Brock, H.W. (Developmental Biology, 2010)
Polycomb group (PcG) genes are required for heritable silencing of target genes. Many PcG mutants have chromatin bridges and other mitotic defects in early embryos. These phenotypes can arise from defects in S phase or mitosis, so the phenotype does not show when PcG proteins act in cell cycle regulation. We analyzed the cell cycle role of the proximal subunit of Polyhomeotic (PhP) in Drosophila. Time-lapse imaging reveals that chromatin bridges formed during mitosis are able to resolve but sometimes result in chromosome breakage. Chromosome bridging is also observed in canonical cell cycles occurring in larval brains and is therefore not unique to the rapid embryonic cycles. PhP colocalizes with chromatin in S phase but not in mitosis in early embryos, indicating a direct role in DNA synthesis. Time lapse imaging of ph(p) mutants reveals an acceleration of S phase, showing that ph(p) regulates S phase length. Like ph(p) mutations, mutations in DNA damage checkpoints result in S phase acceleration. Consistent with this model, mutations in ph do not affect DNA synthesis rates, but exhibit impaired ability to block cell cycle progression following exposure to gamma-rays. Our data show that the mitotic defects of ph(p) are caused by defects in the DNA damage response that occurs after DNA replication in S phase, and we propose that PhP has a direct role in DNA damage repair.